Integrating Digital Transformation and Technological Innovation for Sustainable Renewable Energy Systems: The Role of AI, IoT, and Blockchain in Enhancing Efficiency and Grid Stability - Ragira Osoro, Edwin (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Renewable energy and grid stability systems are transforming because of digital innovation and novel advancements. This necessitates studying advancements within the renewable energy sector through digital technologies, including artificial intelligence (AI), the Internet of Things (IoT), and blockchain. The advancements allow real-time monitoring, predictive maintenance, and decentralized energy management, thus increasing renewable energy systems’ efficiency, sustainability, and dependability. This review was based on how AI integrated with IoT technology and blockchain improves the operational efficiency of renewable energy systems. The PRISMA 2020 guidelines were adopted in this systematic review, and 433 articles from databases such as IEEE Xplore, Science Direct, Google Scholar, and Springer Link were retrieved. After the inclusion and exclusion criteria, 10 (n=10) articles were selected. The quality assessment of the studies was done using the Critical Appraisal Skills Program (CASP) tool. Among the included studies, 70% (n=7) demonstrated that AI achieved efficiency improvements, IoT role optimization of grids was shown in 60% (n=6) of studies and blockchain impact on energy trading in 50% (n=5). In addition, cost reductions were documented in 80% (n=8) of studies, while 90% (n=9) reported security and regulatory challenges during implementation. The findings revealed that the efficiency of renewable energy and grid stability was improved by adopting digital solutions such as AI, IoT, and Blockchain. However, the gaps demonstrated in the study prompt the need to develop policy interventions and conduct further research to reduce technological and regulatory barriers to a sustainable energy transition.